FTA Highlight No.5 – Food Security and Nutrition - Ickowitz, A.; McMullin, S.; Dawson, Ian K.; Sunderland, T.C.H.; Powell, B.; Nurhasan, M.; Vinceti, B.; Jamnadass, Ramni; Meybeck, A.; Gitz, V. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
FTA’s research provides strong evidence of how forests, agroforestry systems and other multifunctional landscapes contribute to food security and nutrition. They contribute a diversity of nutritious foods, ecosystem services that support agriculture, and income to smallholders. Evidence shows that greater tree cover is associated with greater dietary diversity. Wild and planted trees provide important foods, and forests are key habitats for wildlife and sustain healthy rivers providing fish, both of which also are important for diets. Trees are also an important source of animal fodder. Forests, agroforestry and trees provide resilience and stability in the face of climate and other food system shocks. Despite these important contributions, food trees remain an underutilized resource, ecosystem-level functions of forests and trees to sustain agriculture are often not fully taken into account in land management, and land-use change has a profound impact on diets. FTA has generated scientific findings on all of these contributions of forests and trees to food security and nutrition. It has also shared this knowledge with a range of stakeholders, including local communities, national governments and the international scientific and policy-making communities. This has informed global strategies and discourses on food security and nutrition; global policies on food, particularly through the Committee on World Food Security (CFS); and global discussions and policies on sustainable food systems. This publication provides examples of FTA’s forest- and tree-based solutions and how their implementation on the ground supports better nutrition. FTA’s work on food and nutrition provides evidence for promoting the roles of “polycultural” landscapes in contributing to healthy diets, sustainable food systems and broader planetary health.